Ukraine’s window to the West: The role of international railway connection in Transcarpathia (Zakarpattia) - SavchukIvan G (Hungarian Geographical Bulletin, 2014)
In this paper the role of railway network of Transcarpathia (Zakarpattia) in the international transport connections of Ukraine is investigated. The geopolitical importance and favourable transit location of this region within Ukraine along the international boundaries with Hungary, Romania and Slovakia, is well-known. The paper first focuses on the role of natural, political and transport factors in the development of railway network in the region from a historical perspective. Then the importance of railway network in Transcarpathia for the development of international freight traffic in the USSR is highlighted. The role of geopolitical interests in the past and present is demonstrated. The analytical part of the paper focuses on the latest changes in international freight traffic in the region in the period of 2008-2011, and major obstacles in its development are also discussed. The peculiarities of international freight traffic passing through border freight stations of the given region and the contiguous countries are assessed.